Black holes in galactic centers: Quasinormal ringing, grey-body factors and Unruh temperature - R.A. Konoplya (Physics Letters B, 2021)
Recently, Cardoso et al. [1] found an exact solution describing the black hole immersed in a galactic-like distribution of matter. There, the properties of gravitational radiation were studied. Here we continue analysis of properties of this geometry via consideration of the electromagnetic radiation. We calculate quasinormal modes, asymptotic tails and grey-body factors for electromagnetic radiation. In addition, we discuss the Unruh temperature for this spacetime. Estimations made in the regime which is best fitting the galaxies behavior show that influence of the environment on classical and quantum radiation around such black holes must be relatively small.